ODONTOGENIC INFECTION AS A HIDDEN ROUTE OF GENERALIZED TETANUS IN THE INTENSIVE CARE UNIT: CASE REPORT - Nintyas, Felantina Restyar; Anna, Anastasia; Kosasih, Cecep Eli (Padjadjaran Acute Care Nursing Journal, 2025)
Tetanus, an infection caused by Clostridium tetani, remains a global health concern due to its high fatality, morbidity, and mortality rates. Although the spores of this bacterium are commonly found in soil and animal waste, contamination of the oral cavity due to poor oral hygiene and inadequate dental care also presents a significant risk. The aim of this study was to describe the role of dental infection in the incidence of tetanus in the intensive care unit. This study used descriptive study design with case report method. A 67-year-old male patient was admitted for 38 days to the intensive care unit of a government hospital in Bandung due to grade III generalized tetanus, with Ablett grade IV classification and Tetanus Severity Score (TSS) of 7. The patient had a history of stab wounds from wood and multiple plaque (+) in the oral cavity due to poor oral hygiene and had a habit of cleaning teeth using sticks that were not clean and not in accordance with recommended dental care tools.. History of tetanus vaccine with incomplete dose. During treatment, the patient required mechanical ventilator assistance with CPAP-PS mode. Conclusion of this research that the route of entry for tetanus-causing bacteria can be through wounds, including wounds in the oral cavity that often go unnoticed. Therefore, it is very important to maintain oral hygiene through the application of proper oral hygiene and eliminate the habit of cleaning teeth with dirty tools.